PENGARUH SPESIALISASI INDUSTRI AUDITOR DAN REPUTASI AUDITOR TERHADAP AUDIT REPORT LAG (Studi Empiris Pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2016,2017 dan 2018) - Victoria Jeniffer Raya; Herry Laksito (Diponegoro Journal of Accounting, 2020)
The purpose of this research is to empirically examine the relationship between auditor industry specialization and auditor reputation on audit report lag of banking companies listed on Indonesia Stock Exchange (BEI) in 2016, 2017, 2018. This research uses secondary data with a purposive sampling method to select the financial statements of banking companies in 2016 2017, 2018 which are listed on Indonesia Stock Exchange. There are 40 listed companies with 120 samples used. This research used the multiple regression analysis. The classic assumption test is done first before doing the multiple regression test. This research indicates that the independent variable namely auditor industry specialization has a negative and significant effect on audit report lag, while the auditor's reputation has no effect on audit report lag.